Prediction of the mechanical properties of concrete incorporating simultaneous utilization of fine and coarse recycled aggregate - Joseph, Herbert Sinduja; Pachiappan, Thamilselvi; Avudaiappan, Siva; Guindos, Pablo (Revista de la Construcción. Journal of Construction, 2023)
The mechanical properties of concrete were optimized using response surface methodology (RSM) and fuzzy logic. The aggregate portion of the concrete was replaced with recycled aggregate to address the environmental problems caused by building demolition wastes. The essential key factors that influenced the suitability of recycled aggregate in concrete applications are the compressive strength (CS), flexural strength (FS), and the split tensile strength (STS). The experiments were designed with nine combinations of two input factors (percentage of coarse and fine recycled aggregates) at different levels 30, 60, and 100%. Furthermore, optimization techniques were used to determine the strong correlations between the variables and the mechanical parameters. Such optimization techniques helped to identify the optimistic maximum strength for replacing 44% coarse and 65% fine recycled aggregate. Using RSM, the maximum strength results were found to be: CS at 7, 28, 56, and 90 days were 23.61, 35.04, 40.02, and 43.63 N/mm2, respectively, FS 3.6 N/mm2 and STS 2.0 N/mm2. The maximum strength parameters were found using fuzzy logic: CS at 7, 28, 56, and 90 days were 23.5, 35.8, 41, and 46.7 N/mm2, respectively, FS 4.13 N/mm2 and STS 1.97 N/mm2. Such optimization can be carried out to lower the material wastage, energy consumption, and expenses for the production.